Differential Pulse Polarographic Analysis of Glyburide in Pure form and Pharmaceutical Formulations - Mandil, Hasna; Alhaj Sakur, Amer; Alulu, Safa (Asian Journal of Chemistry, 2012)
A sensitive method is described for the determination of glyburide as antidiabetic in its pure form and dosage forms. The proposed method depends upon the polarographic activity of glyburide using cyclic voltammogram, direct current polarography, square wave polarography and differential pulse polarography in acetate buffer. At a sweep rate of 100 mV s-1 the cyclic voltammograms showed a well defined cathodic peak with high selectivity. The differential pulse polarography gave a reproducible well defined diffusion controlled peak for each drug at a sweep rate of 10 mVs-1. The reduction peak was used to determine the tested drug concentrations. Whereby a well-defined cathodic wave is produced over the pH range 2-11. The currentconcentration relationship was found to be rectilinear over the range 1-112, 2-80 and 1-40 μM with a RSD of 5.2, 4.4 and 4.8 % using droping mercury electrode, static droping mercury electrode and hanging droping mercury electrode, respectively. The limit of quantitation was 0.645 μM and the limit of detection 0.194 μM using droping mercury electrode. The proposed method was successfully applied to the determination of glyburide in tablets.